2015
DOI: 10.1165/rcmb.2014-0107oc
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cigarette Smoke–Induced Aggresome Formation in Chronic Obstructive Pulmonary Disease–Emphysema Pathogenesis

Abstract: Cigarette smoke (CS) exposure is known to induce proteostasis imbalance that can initiate accumulation of ubiquitinated proteins. Therefore, the primary goal of this study was to determine if first-and secondhand CS induces localization of ubiquitinated proteins in perinuclear spaces as aggresome bodies. Furthermore, we sought to determine the mechanism by which smoke-induced aggresome formation contributes to chronic obstructive pulmonary disease (COPD)-emphysema pathogenesis. Hence, Beas2b cells were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
122
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(137 citation statements)
references
References 79 publications
14
122
0
1
Order By: Relevance
“…In addition, we identified that clearance of these AB using an autophagy inducer carbamazepine not only reduces apoptosis but also controls cigarette smoke (CS)-induced emphysema (51). Hence, recent studies from our group and others (27,51) have identified the potential of autophagy inducer carbamazepine in rescuing both smoke-induced and alpha-1-antitrypsin Z mutation-associated emphysema in COPD.…”
Section: Innovationmentioning
confidence: 92%
See 2 more Smart Citations
“…In addition, we identified that clearance of these AB using an autophagy inducer carbamazepine not only reduces apoptosis but also controls cigarette smoke (CS)-induced emphysema (51). Hence, recent studies from our group and others (27,51) have identified the potential of autophagy inducer carbamazepine in rescuing both smoke-induced and alpha-1-antitrypsin Z mutation-associated emphysema in COPD.…”
Section: Innovationmentioning
confidence: 92%
“…We recently identified proteostasis/autophagy impairment as a novel central mechanism leading to aggresome formation and subsequent downstream effects such as apoptosis in COPDemphysema (41,51). We and others have identified the global impact of first-and second-hand smoke exposure on overall protein synthesis, ubiquitination, and aggregation of misfolded proteins in perinuclear spaces as aggresome bodies (AB) leading to a unique pathology associated with severity of emphysema in COPD subjects (21,23,35,51,56,58). In addition, we identified that clearance of these AB using an autophagy inducer carbamazepine not only reduces apoptosis but also controls cigarette smoke (CS)-induced emphysema (51).…”
Section: Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…71 Similar to our findings in the diacetyl-exposed lung, ubiquitinated protein aggregates and the corresponding human protein, SQSTM1, accumulate in humans with chronic obstructive pulmonary disease. 72,73 Cigarette smoke is implicated in these aggregates in humans with chronic obstructive pulmonary disease. 72 Because our study demonstrates that diacetyl alters proteostasis and cigarette smoke contains diacetyl, 74,75 the results suggest that diacetyl may play a role in chronic obstructive pulmonary disease in addition to its role in flavorings-related lung disease.…”
Section: Protein Damage and Diacetyl Cytotoxicitymentioning
confidence: 99%
“…72,73 Cigarette smoke is implicated in these aggregates in humans with chronic obstructive pulmonary disease. 72 Because our study demonstrates that diacetyl alters proteostasis and cigarette smoke contains diacetyl, 74,75 the results suggest that diacetyl may play a role in chronic obstructive pulmonary disease in addition to its role in flavorings-related lung disease. 11,12 In addition, during autophagy, SQSTM1 is phosphorylated, a process that activates the Kelch-like ECHassociated protein 1 (Keap1)enuclear factor E2erelated factor 2 (Nrf2) pathway.…”
Section: Protein Damage and Diacetyl Cytotoxicitymentioning
confidence: 99%